Nuna: Naming the Inuit land, imagining indigenous community - Pongérard, Julien (Journal of Northern Studies, 2018)
The Inuit land is often known through Western phrasings such as the “Arctic” or the “Great North.” In this article, based on an extensive review of literature, I focus on the name the Inuit give to their own land, which is one of the only words common to all Inuit dialects: nuna. Studying the word’s meaning casts light on a peculiar indigenous territoriality, and on the centrality of environment in Inuit ways of life and holism thinking. The Inuit conceptualize their inhabiting of the circumpolar region in a way radically opposed to Western narratives of wilderness or wasteland. In the late twentieth century, nuna was turned into a key component of identity politics. Inuit peoples linguistically reappropriated their lands, in parallel with formal land claims and the recognition of Inuit self-governed territories. Nuna is at the core of these processes, as the concept justifies the claims for recognition of vernacular toponyms, and the vocable itself was included in the names of Inuit regions. Nuna as an indigenous political banner helps understanding the imagination of Inuit political communities, emerging from a dialectical co-construction of identities and territories mediated through the linguistics of place.